1993
DOI: 10.1104/pp.102.4.1351
|View full text |Cite
|
Sign up to set email alerts
|

Cotton Cotyledon cDNA Encoding a Peroxidase

Abstract: The GenBank accession number for the sequence reported in this article (GrmM4 cDNA E39) is L08199. LITERATURE ClTED Bednarek SY, Wilkins TA, Dombrowski JE, Raikhel NV (1990) A carboxy-terminal propeptide is necessary for proper sorting of barley lectin to vacuoles of tobacco. Plant Cell 2: 1145-1155 Chrispeels MJ (1991) Sorting of proteins in the secretory system. Annu Rev Plant Physiol Plant Mo1 Biol42: 21-53 Hughes DW, Galau GA (1989) Temporally modular gene expression during cotyledon development. Genes Dev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

1995
1995
2014
2014

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 4 publications
0
3
0
Order By: Relevance
“…One shows 85% identity to a secretory peroxidase thought to be involved in response to several different stresses (Tognolli et al 2002) and that is highly homologous to a peroxidase upregulated in response to salt stress in cotton (Ritter et al 1993). Another shows homology to a heat-shock protein from Arabidopsis.…”
Section: Discussionmentioning
confidence: 99%
“…One shows 85% identity to a secretory peroxidase thought to be involved in response to several different stresses (Tognolli et al 2002) and that is highly homologous to a peroxidase upregulated in response to salt stress in cotton (Ritter et al 1993). Another shows homology to a heat-shock protein from Arabidopsis.…”
Section: Discussionmentioning
confidence: 99%
“…PODs have been associated with high salinity stress in a few plants. Ritter et al (1993) demonstrated a peroxidase mRNA was induced 3fold in the young leaves of saltstressed cotton plants. Kumar et al (2011) indicated that the expression levels of CrPrx3 and CrPrx4, two new class III POD genes, were downregulated in Catharanthus roseus under salt stress.…”
Section: Discussionmentioning
confidence: 98%
“…malvacearum (Delannoy et al 2003(Delannoy et al , 2005. POD8 is an anionic peroxidase predicted to be associated with the apoplast or cell wall (Delannoy et al 2006;Ritter et al 1993) and shows almost exclusive expression in cotton roots (Delannoy et al 2006). POD4 and POD8 transcript levels in roots of control and RKN-infected M315 and M8 plants were measured by qRT-PCR.…”
Section: Temporal Expression Of Defense-related Genes Following Rkn Imentioning
confidence: 98%